Bony Fixation of the Nasal Framework - Haack, Sebastian; Hacker, Stefan; Mann, Steven; Gubisch, Wolfgang (Facial Plastic Surgery, 2019)
The importance of a straight and stable central framework is beyond dispute. Many authors allude to technical aspects how to achieve the above-mentioned requirements. Far less is said about the contact zones of the framework and how to achieve a long-lasting and solid fixation. In the authors' patient group, they found the need to work on the septum/the central framework in approximately 84% of the cases. In 61% of the patients, the authors had to operate on the fixation point. Of course, there is a great variety of anatomical findings. So the required techniques differ immensely. The surgeon must be prepared for all kinds of different situations. Especially the dorsal fixation and the anchoring on the maxilla without having a standard anterior nasal spine can be a great challenge. In their daily routine, suture techniques (e.g., the transcutaneous transosseous cerclage suture) have become the authors' working horse for these complex fixation situations.
Keywords: septal fixation; bony framework; anterior nasal spine; TTC suture